Peran Ormas Islam dalam Pembinaan Remaja - Siswoyo; Moh. Subhan (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2021)
Teenage is an unique phase of life, a transition from child hood to adult. In this transition, teenager often become confuses to determine his self and future. In this confusion, teenager becomes focus of attention, from parent, family, school or Islamic social organization. There’s several reason Islamic social organization have attention to teenage, one of it is because they have attention to religion, social, and community problems. Their role is by routine and planned religious teaching.